A Cointegration Analysis of Broad Money Demand in Cameroon - Nachega, Jean-Claude (IMF Working Papers; Working Paper ;, 2001)
This paper applies cointegration analysis and error-correction modeling to investigate the behavior of broad money demand in Cameroon over 1963/64-1993/94. The cointegrated VAR analysis first describes an open-economy model of money, prices, income, and a vector of rates of return, within which three steady state relations are identified: a stable money demand function, an excess aggregate demand relationship, and the uncovered interest rate relation under fixed exchange rates and perfect capital mobility. Empirical support is thereafter provided for both PPP and the international Fisher parity between Cameroon and France, and the stability of the short-run dynamics of the broad money demand function is confirmed.